Unraveling the contribution of climatic heterogeneity on evolutionary processes within oophaga poison dart frogs (2017)
Understanding the role of climatic factors on diversification processes remains among the pivotal questions in ecology and evolutionary biology. The main goal of this study was to approach this question at different temporal and spatial scales within a convenient model: the egg-feeding poison frogs in the genus Oophaga and their relatives. I first constructed a phylogeographic hypothesis on the evolution of Oophaga pumilio lineage. Phylogeographic analysis suggest that the Nicaraguan populations originated by a Late Pleistocene range expansion northwards, and reconstructs the origin of the species in southeastem Costa Rica. I investigated geographic variation in physiological traits linked to the regulation of evaporative water loss and tested for correlations with current and past climatic heterogeneity